A feasibility study to assess the design of a multicentre randomized controlled trial of the clinical and cost-effectiveness of a caregiving intervention for people following hip fracture surgery. (1st November 2021) - Smith, Toby; Clark, Lucy; Khoury, Reema; Man, Mei-See; Hanson, Sarah; Welsh, Allie; Clark, Allan; Hopewell, Sally; Pfeiffer, Klaus; Logan, Pip; Crotty, Maria; Costa, Matthew; et al.
Abstract : Aims: This study aims to assess the feasibility of conducting a pragmatic, multicentre randomized controlled trial (RCT) to test the clinical and cost-effectiveness of an informal caregiver training programme to support the recovery of people following hip fracture surgery. Methods: This will be a mixed-methods feasibility RCT, recruiting 60 patients following hip fracture surgery and their informal caregivers. Patients will be randomized to usual NHS care, versus usual NHS care plus a caregiver-patient dyad training programme (HIP HELPER). This programme will comprise of three, one-hour, one-to-one training sessions for the patient and caregiver, delivered by a nurse, physiotherapist, or occupational therapist. Training will be delivered in the hospital setting pre-patient discharge. It will include practical skills for rehabilitation such as: transfers and walking; recovery goal setting and expectations; pacing and stress management techniques; and introduction to the HIP HELPER Caregiver Workbook, which provides information on recovery, exercises, worksheets, and goal-setting plans to facilitate a 'good' recovery. After discharge, patients and caregivers will be supported in delivering rehabilitation through three telephone coaching sessions. Data, collected at baseline and four months post-randomization, will include: screening logs, intervention logs, fidelity checklists, quality assurance monitoring visit data, and clinical outcomes assessing quality of life, physical, emotional, adverse events, and resource use outcomes. The acceptability of the study intervention and RCT design will be explored through qualitative methods with 20 participants (patients and informal caregivers) and 12 health professionals. Discussion: A multicentre recruitment approach will provide greater external validity across population characteristics in England. The mixed-methods approach will permit in-depth examination of the intervention and trial design parameters. The findings will inform whether and how a definitive trial may be undertaken to test the effectiveness of this caregiver intervention for patients after hip fracture surgery. Cite this article: Bone Jt Open 2021;2(11):909–920.